The Development of Chemical Learning Based on Chemical Commissions to Improve Concept Mastery and Students’ Creative Thinking - Hisar Marulitua Manurung; Juni Agus Simaremare (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study aims to develop comic chemistry-based learning to improve students' conceptual mastery and creative thinking on the colligative properties of solutions (SKL). In this study, the development of chemical comic media was validated and tested on a small and large scale. Data on student learning outcomes which include cognitive, affective, and psychomotor aspects were collected using the test and observation method with observation sheets. From the data obtained, the magnitude of the influence of chemical comic media on students' creative thinking skills and mastery of concepts was 38.03% and 22.17%, respectively. Mastery of concepts and creative thinking in the experimental class was higher than in the control class. The difference in concept mastery and creative thinking was due to the use of chemical comics learning media to attract students' attention to learning and make teaching and learning more enjoyable. This study concluded that there was an effect of using comics media that has been developed on the creative thinking power and mastery of students' concepts on the colligative properties of solutions.